Influence of boundary layer dynamics and isoprene chemistry on the organic aerosol budget in a tropical forest. Issue 16 (20th August 2013) - Janssen, R. H. H.; Vilà‐Guerau de Arellano, J.; Jimenez, J. L.; Ganzeveld, L. N.; Robinson, N. H.; Allan, J. D.; Coe, H.; Pugh, T. A. M.
Abstract : [1] We study the organic aerosol (OA) budget in a tropical forest by analyzing a case that is representative for the OP3 campaign at Borneo. A model is designed that combines the essential dynamical and chemical processes that drive the diurnal evolution of reactants in the atmospheric boundary layer (BL). In this way, the model simultaneously represents the effects and interactions of various dynamical and chemical factors on the OA budget. The model is able to reproduce the observed diurnal dynamics of the BL, including the evolution of most chemical species involved in secondary organic aerosol (SOA) formation. A budget analysis of the contributions of the dynamic and chemical processes reveals the significance of the entrainment process in the diurnal evolution of SOA. Further, we perform a series of sensitivity analyses to determine the effect of meteorological forcings and isoprene chemical pathways on the OA budget. Subsidence and advection of cool air have opposing effects on the OA concentration, although both suppress BL growth. Recycling of the OH radical in the oxidation of isoprene may affect the amount of SOA that is formed, but must be understood better before its impact can be definitely determined. SOA formation from isoprene is calculated for both the low‐ and high‐NOx pathway, with the latter dominating the isoprene peroxy radical chemistry. Finally, we study the significance of SOA formation through the reactive uptake of isoprene epoxydiols on acidic sulfate aerosol. Despite the incorporation of these new pathways, the OA concentration is systematically underestimated by about a factor of 2. Key Points: Contribution of BL dynamics and chemistry on organic aerosol budget is analyzed Entrainment important for diurnal evolution organic aerosol Despite new isoprene SOA pathways, OA is underestimated by factor 2